Research Ethics in Publication - Parawansah, Rosa Indah; Mukhlis, Imam (CV. Lenggogeni Data Publishing, 2023)
Moral teaching is the teaching of human good based on the dignity of each person as a human being, and ethics is a branch of philosophy that critically considers which actions are good or bad based on certain moral teachings. On the other hand, research is a series of processes to answer research questions. To determine the readiness of researchers to answer research questions in a sensible and understandable way, research design is crucial. However, publication is the final stage of research, where research results are written and communicated to the public. It has become a very valuable thing for researchers to understand their contribution in particular research. Research methodology, research process, and publication are the three main components of research ethics. Ethics related to research methodologies can include such things as the confidentiality of respondents' data, their desires and expectations to participate in research, and close relationships between researchers and respondents. Ethics relating to research processes also includes issues such as data falsification, fabrication, scientific freedom, integrity and transparency. However, problems related to the publication of research findings may include plagiarism and many submissions.